DISTINCTION OF SOCIAL AND PUBLIC RELATIONS IN SOCIETY - Kovalova, Darina (Scientific Journal of Polonia University, 2023)
Mastering of the “sociology” major by domestic students takes place in accordance with the curricula approved by the management of each university, taking into account the normative documents of the Ministry of Education and Science of Ukraine. Therefore, modern applicants (students) are initially inclined to functionalism and systemic theory in sociology, offering to study the works of the classics of sociology of the end of the 19th century – the beginning of the 20th century. However, the applicants will later learn about theoretical polyparadigmism in modern sociology and the possibility to choose not only classical concepts for the implementation of their scientific developments. This possibility was a consequence of the fact that changes were taking place in the paradigm of system theory. This influenced the evolution of sociological theorizing. Therefore, the above now affects the choice of applicants, post-graduate students and doctoral students of the basic concept for their sociological explorations, in order to avoid accusations of ignorance of modern sociological theory. The situation, as a rule, has two contradictory sides. So, on the one hand, there are classical instructions or settings for scientists to carry out their cognitive procedures (for example, diagnosis, classification, stratification, typology, or systematization in general). On the other hand, alternative post-classical foundations have already been proposed, which are rather only outlined in most textbooks and textbooks on sociology, and therefore deserve in-depth study in order to reveal their diverse potential (heuristic, diagnostic, methodological, etc.).